Linkage of Equatorial Ionization Anomaly With the Day‐To‐Day Occurrence of Postsunset Irregularities and Scintillation in Low‐Latitude Region Around 110°E - Weihua Luo; Heng Li; Chao Xiong; Zhengping Zhu; Xiao Yu; Shanshan Chang (Space Weather)
Abstract The zonal electric field and meridional wind are two major factors to affect the formation of both equatorial ionization anomaly (EIA) and plasma irregularities in equatorial and low‐latitude regions, the correlation between the EIA characteristics and the occurrence of both irregularities and the sequent scintillation is always concerned. In this study, we investigated the relationship between the day‐to‐day occurrence of scintillation based on ground‐based GPS observations at Sanya (18.3°N, 109.6°E; dip lat.: 12.8°N) and Hongkong (22.4°N, 114.2°E; dip lat.: 16.1°N), China, and day‐to‐day variations of EIA inferred from the Gravity Recovery and Climate Experiment observations in equinoctial months (March‐April and September‐October) during high solar activities (2012–2014). The results indicated that EIA strength can be linked with the day‐to‐day occurrence of post‐sunset irregularities and scintillation, and post‐sunset scintillation would be likely to occur as electron density above the EIA trough is low and EIA is strong. There are other key factors to affect the initiation and evolution of irregularities besides zonal electric field and meridional wind, such as seed perturbations or wave‐like structures. The day‐to‐day variations of electron density in EIA regions, EIA strength and EIA asymmetry were not well correlated quantitatively with the scintillation intensity representing by daily S4 maximum in low‐latitude region. These results can help us understand and predict the day‐to‐day variability of irregularities and scintillation in equatorial and low‐latitude regions.